Parameters of weed management under different cropping systems in Uttar Pradesh - Singh, Randhir; Kumar, Anuj; Sendhil, R; Singh, Satyavir; Chand, Ramesh; Verma, Ramesh Pal Singh; Sharma, Indu (Journal of Cereal Research, 2014)
Data were collected during 2012-13 from a randomly selected 334 farmers through a multi-stage and proportionate sampling across the selected districts of Moradabad, Sambhal and Bulandsahar of Uttar Pradesh to devise weed management strategies in wheat crop. Ricewheat, sugarcane-wheat, maize-wheat, urd-wheat and bajra-wheat were the main crop rotations in the sampling areas. Majority of the farmers were middle aged, literate, lived in joint families, had membership of some organization (mainly cooperative societies) and more than 10 years of experience in agriculture. They sought information regarding cultivation of wheat crop from other farmers, agriculture officers, newspapers, TV and input dealers. Most of the farmers had purchased seed from government agencies and private input dealers apart from using their own seed.Most of the farmers had applied herbicides to control weeds across the crop rotations wherein Mandusi (Phalaris minor) and Bathua (Chenopodium album) emerged as the major weeds. They used knapsack sprayers fitted with cut nozzle for application of herbicides. About half of them sprayed herbicides themselves. Merely 5.39 percent of the farmers had increased dose of herbicide over last year. Only 2.40 percent of the farmers had used herbicide twice during the crop season. Majority of the farmers had applied 2,4-D (44-60%) and sulfosulfuron (11.54-52%) across crop rotations. Isoproturon has been applied by the farmers to control Phalaris minor. Irrespective of level of education, some of the farmers were aware of different agronomic management practices to control weeds. None of the farmers had adopted zero tillage and residue retention as a strategy to control weeds in wheat crop. They need to be educated about timely sowing (Last week of October to 20th November), zero tillage technique, timely and uniform spray using flat fan nozzle, herbicides rotation and crop rotation strategies to control weeds.